2015
DOI: 10.1126/sciadv.1500603
|View full text |Cite
|
Sign up to set email alerts
|

Regulated lysosomal exocytosis mediates cancer progression

Abstract: LAMP1 oversialylation results in excessive lysosomal exocytosis, promoting tumor invasion and drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
142
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 59 publications
2
142
0
2
Order By: Relevance
“…17 The spatial and temporal control of membrane dynamics is essential for cellular processes and may underly pathologies, as for example lysosomes are distributed toward the plasma membrane to promote invasion and metastasis in some cancer cells. 18 Our findings provide insight into Klp98A as a novel player in autophagic vesicle movement and maturation, which acts as a scaffold protein though its interdependent domains. Klp98A may act as a focal point for multiple regulatory signals.…”
mentioning
confidence: 79%
“…17 The spatial and temporal control of membrane dynamics is essential for cellular processes and may underly pathologies, as for example lysosomes are distributed toward the plasma membrane to promote invasion and metastasis in some cancer cells. 18 Our findings provide insight into Klp98A as a novel player in autophagic vesicle movement and maturation, which acts as a scaffold protein though its interdependent domains. Klp98A may act as a focal point for multiple regulatory signals.…”
mentioning
confidence: 79%
“…In another study on rhabdomyosarcoma, data showed that lysosomal exocytosis, which is positively correlated with the release of exosomes, could be induced to transform tumor cells to an invasive and drug-resistant phenotype by downregulation of NEU1 (target of sialidase) and accumulation of LAMP1 (sialylated membrane glycoprotein) [67]. To determine the mechanism of NEU1-LAMP1 controlling lysosomal exocytosis in sarcoma, human rhabdomyosarcoma cell lines RH41 with higher-NEU1 and lower-LAMP1 expression and RH30 with lower-NEU1 and higher-LAMP1 expression were examined and compared [67].…”
Section: Roles Of Exosomes In Sarcomamentioning
confidence: 99%
“…To determine the mechanism of NEU1-LAMP1 controlling lysosomal exocytosis in sarcoma, human rhabdomyosarcoma cell lines RH41 with higher-NEU1 and lower-LAMP1 expression and RH30 with lower-NEU1 and higher-LAMP1 expression were examined and compared [67]. In both RH41 and RH30 cells, exosomes were isolated through ultracentrifugation and detected by positive expression of exosomal markers flotillin-1, CD81, syndecan-1, and syntenin-1; however, more exosomes were observed to be secreted by RH30 cells [67]. In RH30 cells, more lysosomes were found tethered to or docked at the plasma membrane and showed a stronger trend for exocytosis [67].…”
Section: Roles Of Exosomes In Sarcomamentioning
confidence: 99%
See 2 more Smart Citations